Regulatory Role of Cystathionine-γ-Synthase and de novo Synthesis of Methionine in Ethylene Production during tomato Fruit Ripening - Katz, Y.S; Galili, G; Amir, R (Plant molecular biology, 2006)
The essential amino acid methionine is a substrate for the synthesis of S-adenosyl-methionine (SAM), that donates its methyl group to numerous methylation reactions, and from which polyamines and ethylene are generated. To study the regulatory role of methionine synthesis in tomato fruit ripening, which requires a sharp increase in ethylene production, we cloned a cDNA encoding cystathionine γ-synthase (CGS) from tomato and analysed its mRNA and protein levels during tomato fruit ripening. CGS mRNA and protein levels peaked at the “turning” stage and declined as the fruit ripened. Notably, the tomato CGS mRNA level in both leaves and fruit was negatively affected by methionine feeding, a regulation that Arabidopsis, but not potato CGS mRNA is subject to. A positive correlation was found between elevated ethylene production and increased CGS mRNA levels during the ethylene burst of the climacteric ripening of tomato fruit. In addition, wounding of pericarp from tomato fruit at the mature green stage stimulated both ethylene production and CGS mRNA level. Application of exogenous methionine to pericarp of mature green fruit increased ethylene evolution, suggesting that soluble methionine may be a rate limiting metabolite for ethylene synthesis. Moreover, treatment of mature green tomato fruit with the ethylene-releasing reagent Ethephon caused an induction of CGS mRNA level, indicating that CGS gene expression is regulated by ethylene. Taken together, these results imply that in addition to recycling of the methionine moieties via the Yang pathway, operating during synthesis of ethylene, de novo synthesis of methionine may be required when high rates of ethylene production are induced.